Uzlah as a Qur'anic-Based Digital Detox Paradigm: Digital Literacy Strategies in Facing the Phenomenon of Brain Rot - Hamdani, Sofia; Muslim HD, Ahmad Tri (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The phenomenon of brain rot, which arises from the rapid, superficial, and excessive consumption of digital content, has become a serious problem that affects the cognitive, emotional, social, and spiritual quality of the younger generation. This study aims to examine the relevance of the concept of uzlah to modern digital detox practices and to offer a Qur'an-based digital detox concept inspired by the concept of uzlah as a digital literacy strategy in dealing with the phenomenon of brain rot. The focus of the study is directed at understanding digital detox as a form of uzlah today. This research is a library-based qualitative study. Primary data sources include Quranic verses related to the concept of uzlah and their interpretations in classical and contemporary tafsir. Secondary data consists of peer-reviewed journal articles, academic books, and prior studies on digital behavior, digital detoxification, and brain damage. Data were collected through documentation and a systematic literature review, then analyzed using descriptive qualitative analysis. The results of the study show that uzlah contains three main principles, namely tazkiyatun nafs (purification of the self), tafakkur (contemplation), and mujāhadah an-nafs (control of the desires). All three are in line with the needs of modern humans to restore balance in their lives amid technological pressures. The integration of uzlah values into the practice of digital detox has given rise to a new paradigm called Qur'anic-based digital uzlah, which is a spiritual approach that combines technological awareness with divine values. This paradigm positions digital uzlah as a form of transformative Qur'anic literacy, encompassing four stages: intention (an-niyyah), selective withdrawal (at-ta’zil), purification (tazkiyah), reflection (tafakkur), and reintegration (i‘ādat al-‘amal). Through these stages, humans are guided to use technology consciously, ethically, and spiritually, making digital activities part of their devotion to Allah. Thus, uzlah as a Qur'anic-based digital detox paradigm is not intended to distance oneself from the modern world, but rather as a spiritual strategy to rearrange the relationship between humans and technology, themselves, and God.